Transcriptional analysis of the vanC cluster from Enterococcus gallinarum strains with constitutive and inducible vancomycin resistance (2005)
The vanC glycopeptide resistance gene cluster encodes enzymes required for synthesis of peptidoglycan precursors ending in d-Ala-d-Ser. Enterococcus gallinarum BM4174 and SC1 are constitutively and inducibly resistant to vancomycin, respectively. Analysis of peptidoglycan precursors in both strains indicated that UDP-MurNAc-tetrapeptide and UDP-MurNAc-pentapeptide[d-Ser] were synthesized in E. gallinarum SC1 only in the presence of vancomycin (4 μg/ml), whereas the “resistance” precursors accumulated in the cytoplasm of BM4174 cells under both inducing and noninducing conditions. Northern hybridization and reverse transcription-PCR experiments revealed that all the genes from the cluster, vanC-1, vanXYC, vanT, vanRC, and vanSC, were transcribed from a single promoter. In the inducible SC1 isolate, transcriptional regulation appeared to be responsible for inducible expression of resistance. Promoter mapping in E. gallinarum BM4174 revealed that the transcriptional start site was located 30 nucleotides upstream from vanC-1 and that the −10 promoter consensus sequence had high identity with that of the vanA cluster. Comparison of the deduced sequence of the vanSC genes from isolates with constitutive and inducible resistance revealed several amino acid substitutions located in the X box (R200L) and in the region between the F and G2 boxes (D312N, D312A, and G320S) of the putative sensor kinase proteins from isolates with constitutive resistance.